2003
DOI: 10.1073/pnas.1031047100
|View full text |Cite
|
Sign up to set email alerts
|

The nuclear pore complex protein ALADIN is mislocalized in triple A syndrome

Abstract: Triple A syndrome is a human autosomal recessive disorder characterized by an unusual array of tissue-specific defects. Triple A syndrome arises from mutations in a WD-repeat protein of unknown function called ALADIN (also termed Adracalin or AAAS). We showed previously that ALADIN localizes to nuclear pore complexes (NPCs), large multiprotein assemblies that are the sole sites of nucleocytoplasmic transport. Here, we present evidence indicating that NPC targeting is essential for the function of ALADIN. Chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
121
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(125 citation statements)
references
References 22 publications
4
121
0
Order By: Relevance
“…Up to now, all investigated naturally occurring pathogenic AAAS mutations result in mislocalization of ALADIN away from the NPC to a predominantly cytoplasmic distribution. 6,7 Although the mutants ALADIN Q15K and ALADIN L25P were previously described as apparently remaining at the nuclear pore, 7 ALADIN L25P turned out to be a polymorphism and ALADIN Q15K was discovered to be a missense mutation only in vitro, but in vivo results in aberrant splicing causing a frameshift followed by an early stop codon (p.G14fsX58). 7 We conclude that the leucine 430 mutation does not interfere with the correct targeting of ALADIN to the NPC but may rather be critical for the interaction of ALADIN with other protein(s) of the nuclear Before the discovery of AAAS mutations as the molecular cause for the triple A syndrome, it had already been pointed out that the significant neurological problems are common in this multisystem disorder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to now, all investigated naturally occurring pathogenic AAAS mutations result in mislocalization of ALADIN away from the NPC to a predominantly cytoplasmic distribution. 6,7 Although the mutants ALADIN Q15K and ALADIN L25P were previously described as apparently remaining at the nuclear pore, 7 ALADIN L25P turned out to be a polymorphism and ALADIN Q15K was discovered to be a missense mutation only in vitro, but in vivo results in aberrant splicing causing a frameshift followed by an early stop codon (p.G14fsX58). 7 We conclude that the leucine 430 mutation does not interfere with the correct targeting of ALADIN to the NPC but may rather be critical for the interaction of ALADIN with other protein(s) of the nuclear Before the discovery of AAAS mutations as the molecular cause for the triple A syndrome, it had already been pointed out that the significant neurological problems are common in this multisystem disorder.…”
Section: Discussionmentioning
confidence: 99%
“…5 Although the precise function of ALADIN has not yet been elucidated, it was shown that the correct localization of ALADIN at the nuclear pore plays an important role for its function. 6,7 All naturally occurring pathogenic mutations investigated so far resulted in a mislocalization of the mutant ALADIN protein in the cytoplasm or in an even distribution between the nucleus and cytoplasm.…”
Section: Introductionmentioning
confidence: 99%
“…Often patient presents with potentially episode of fatal hypoglycaemia. In this syndrome, there are autonomic neurological abnormalities associated with three other symptoms including alacrima, achalasia and adrenal insufficiency named as 4S syndrome (18).…”
Section: Discussionmentioning
confidence: 99%
“…Identification of ALADIN as a component of NPCs facilitated a more detailed analysis of the molecular basis of mutations causing the disease. It has been declared that characterization of an ALADIN mutant cell line indicates that the absence of functional ALADIN cannot produce morphological abnormalities in nuclei, NPCs or NEs, indicating that the defect is functional rather than structural (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation